56.6k views
5 votes
Tính đạo hàm y= ( x^2+1)(X^3+1)(x^4+1)

1 Answer

2 votes

Use the product and power rules:


y = (x^2+1)(x^3+1)(x^4+1)

The product rule says


(\mathrm dy)/(\mathrm dx) = (\mathrm d(x^2+1))/(\mathrm dx)(x^3+1)(x^4+1) + (x^2+1)(\mathrm d(x^3+1))/(\mathrm dx)(x^4+1) + (x^2+1)(x^3+1)(\mathrm d(x^4+1))/(\mathrm dx)

and using the power rule to compute the remaining derivatives gives


(\mathrm dy)/(\mathrm dx) = \boxed{2x(x^3+1)(x^4+1) + 3x^2(x^2+1)(x^4+1) + 4x^3(x^2+1)(x^3+1)}

User Thebiffboff
by
4.7k points